Imposto sobre a renda e resultados positivos de controladas e coligadas no exterior - Gavaldão Junior, Jayr Viégas (2008)
This paper aims at analyzing the effectiveness of the current normative system which determines the inclusion of amounts related to profits gained abroad by controlled or colligated corporations in the calculation basis of the Brazilian income tax. For this purpose, it is created an interpretative proposal which considers the Law to be a text, and enforces the role of the reader/interpreter as a participant in making sense within the communicational process. The proposal is preceded by the Law genesis approach, as a cultural object and resulting in the need of preserving the social life. At this point, it is given special attention to the understanding of the Law as a language for guiding behaviors, which essence lies in must-be, acting on prevailing values. Assuming this role, the prescriptive language promotes conscious stimulations on its receivers, as says Jhering. After the delimitation of the methodological premises, there is the contact with the Positive Law text, and such stage starts with analyzing the constitutional taxation system, going to the incidence structural rule and to the income tax regime, within the constitutional and National Taxation Code texts. Within the latter, the concept availability is approached, explaining its uselessly for the definition of income tax, which is constitutionally resolved. It is also observed, in such legal text, for treating the profits earned abroad. Later, it is visited the international experience in which is the transparency rule model. Then, the Brazilian normative treatment is analyzed, provided the positive results of foreign controlled or colligated, since the opening adoption period of the universality criteria, for corporation. Finally, the text present in the Art. 74 of the Provisory Measure 2.158/2001, disconsidering the subject to which the reader is conducted by the textual instructions. It results in the discovery of the hidden speech with a different meaning, from which it is build the invalid tax rule, distant from the system